The Effect Of Exercises In Developing Some Offensive And Defensive Skills By Using The Automatic Fencer Of The Fencing Weapon - Qasim Mohammed Ibrahim, Atheer (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed to identify on the effect Exercise using the automatic fencing device for some offensive and defensive skills in the sport of fencing, as the player needs these skills during the match because the defense is a prelude to the process of responding and attacking in various competitions, as well as accelerating the pace of play, and the study was based on the experimental method, as the researcher chose the method of the two control groups The study was conducted on a sample of (6) players from Diyala club teams (youth category), and after implementing the training program, the results of the tribal and remote tests were collected for the variables of the study under study. The researcher deliberately processed the results statistically using the statistical bag ( spss ). It was concluded that the exercises using the device had a positive impact on the development of some offensive and defensive skills of the study sample, and the study recommended Focusing on equipment and aids when developing training programs because of their positive impact on fencing players and their great importance during the match and moving away from the traditional methods used in training.